2021
DOI: 10.3390/foods10112807
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Oxidative Stress-Induced Apoptosis by Fermented Sea Tangle (Laminaria japonica Aresch) in Osteoblastic MC3T3-E1 Cells through Activation of Nrf2 Signaling Pathway

Abstract: The purpose of the present study was to explore the efficacy of fermented extract of sea tangle (Laminaria japonica Aresch, FST) with Lactobacillus brevis on DNA damage and apoptosis in hydrogen peroxide (H2O2)-stimulated osteoblastic MC3T3-E1 cells and clarify related signaling pathways. Our results showed that exposure to FST significantly improved cell viability, inhibited apoptosis, and suppressed the generation of reactive oxygen species (ROS) in H2O2-stimulated cells. In addition, H2O2 triggered DNA dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…GC-induced apoptosis due to oxidative stress is mediated by ERK1/2 activation in MC3T3-E1 cells [ 85 ] and involves the downregulation of Nrf2 in BMSCs [ 86 ]. It is possible that, in osteoblasts, there is a correlation between the reduced activation of Nrf2 due to oxidative stress [ 49 ] and ROS-induced apoptosis, considering that the activation of the γNrf2 signaling cascade inhibits oxidative injury and apoptosis in these cells [ 87 , 88 ].…”
Section: Oxidative Stress and Osteoporosis: Principal Involved Molecu...mentioning
confidence: 99%
“…GC-induced apoptosis due to oxidative stress is mediated by ERK1/2 activation in MC3T3-E1 cells [ 85 ] and involves the downregulation of Nrf2 in BMSCs [ 86 ]. It is possible that, in osteoblasts, there is a correlation between the reduced activation of Nrf2 due to oxidative stress [ 49 ] and ROS-induced apoptosis, considering that the activation of the γNrf2 signaling cascade inhibits oxidative injury and apoptosis in these cells [ 87 , 88 ].…”
Section: Oxidative Stress and Osteoporosis: Principal Involved Molecu...mentioning
confidence: 99%
“…Data shows that in the presence of H 2 O 2 , the important metabolites Fermented Sea T angle (FST) of the traditional Chinese medicine Saccharina japonica [Phaeophyceae] significantly promotes nuclear translocation and phosphorylation of Nrf2, accompanied by upregulation of HO-1 expression. Kim et al (Kim et al, 2021) further confirmed that FST inhibits oxidative stress through the Nrf2/HO-1 pathway by pretreating MC3T3-E1 cells with the HO-1 inhibitor zinc protoporphyrin (ZnPP) to block the Nrf2/HO-1 signaling pathway. Studies have shown that pre-treatment with ZnPP significantly abolishes the protective effect of FST on H 2 O 2induced damage in MC3T3-E1 cells.…”
Section: Nrf2/ho-1 Signaling Pathwaymentioning
confidence: 68%
“…Moreover, most glutamic acid in L. japonica is converted to gamma-aminobutyric acid (GABA) [18]. GABA-enriched FST extract not only has antioxidant effects but also prevents or treats diseases, such as cognitive disorders and liver damage [19][20][21][22]. GABA improves skin moisture, skin wrinkles, and epidermal thickness on human skin cells and hairless mice [23].…”
Section: Ivyspringmentioning
confidence: 99%